Experiment on a full-duplex OFDM radio-over-fiber system with 60GHz optical millimeter wave - DONG Ze1; CAO Zi-zheng1; CHEN Lin1; YU Jian-jun1 (Tongxin xuebao)
An integrated full-duplex radio-over-fiber system with 60GHz wireless OFDM mm-wave transmission by using external modulation was proposed and experimentally demonstrated.The experimental results show that the 58GHz optical millimeter-wave will be generated by 29GHz RF resource.2.5Gbit/s OFDM downstream signal are modulated on the 58GHz optical millimeter-wave.The modulated signal can be transmitted over 20km fiber,and 3.3m wireless distance can be realized simultaneously.2.5Gbit/s OOK-NRZ upstream data signals are modulated on the reused central wavelength and transmitted over 20km fiber to the central station.